Risk identification and early warning of disaster-causing organisms in the cooling water intake area of a coastal nuclear power plant - Heming Cui; Hong Zhou; Cunchao Wu; Mingbo Zhao; Xiangyuan Xu; Haiping Li (Marine Pollution Bulletin, 2026)

Machine learning-based geographical origin discrimination of Smilax china - Boyuan Xu; Haotian Zhong; Yan Wang; Rui Liu; Xiao Huang; Heming Wu; Lei Wang; Aiping Deng; Yong Xiao; Kun Yu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

The Mechanical Microenvironment of Trabecular Bones Subjected to a Physiological Gait Load - Yan Wang; Heming Chen; Baopeng Wu; Zhiyong Li; Nicola M. Pugno; Xiaogang Wu; Qiang Chen (Annals of Biomedical Engineering, 2026)

Model-Dependent Attenuation of Seizures by Cinnabar - Yuang Gu; Yu Yao; Qiuwen Lou; Xinyan Zhu; Ju Lan; Chenshu Gao; Shuangshuang Wu; Jingjia Liang; Cenglin Xu; Yi Wang; Heming Cheng; Zhong Chen (Neuroscience Bulletin, 2026)

Detailed investigation and potential instability analysis based on FLAC3D-Massflow: a case study of Majia landslide - Heming Ren; Mingtao Ding; Shuang Liu; Jianbo Wu; Haiguang Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Stability of β-cyclodextrin interface-modified iron-carbon composite and its migration in porous media - Kangping Huang; Tianwen Zheng; Xinyue Li; Ziyin Yang; Ruoxi Li; Yizhou Liu; Naijin Wu; Moxi Wang; Liqin Zhi; Huilong Luo; Wenxia Wei; Peizhong Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Development of novel sustainable lignin nanoparticles-caseinate nanocomposite films with properties for application as food packaging materials - Yitong Li; Haizhu Wu; Yin Zhang; Jun Zhang; Heming Huang; Guanben Du; Bertrand Charrier; Hisham Essawy; Antonio Pizzi; Jingjing Liao; Xiaojian Zhou; Xinyi Chen (Food Hydrocolloids, 2025)

Predicting the flavor potential of green coffee beans with machine learning-assisted visible/near-infrared hyperspectral imaging (Vis-NIR HSI): Batch effect removal and few-shot learning framework - Minping Wu; Zhuangwei Shi; Haiyu Zhang; Rui Wang; Jiayi Chu; Shao Quan Liu; Heming Zhang; Hai Bi; Weihua Huang; Rui Zhou; Chenhui Wang (Food Control, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Rapid identification of defects in doped organic crystalline films via machine learning-enhanced hyperspectral imaging - Lijiao Wu; Wei Wang; Zhuangwei Shi; Haiyu Zhang; Lianbao Ke; Xiaohong Liang; Detian Tian; Heming Zhang; Hai Bi; Wangqiao Chen; Guofu Zhou (Chemical Engineering Journal, 2025)

The synergistic influence mechanism of the alkali metal sodium and CO2 on coal rapid pyrolysis soot: Experiments and DFT calculations - Ziqi Zhao; Jirui Jin; Qian Du; Dun Li; Jianmin Gao; Heming Dong; Yu Zhang; Di Wu; Xiao Yang (Fuel, 2025)

Visually evaluating drug efficacy in living cells using COF-based fluorescent nanoprobe via CHA amplified detection of miRNA and simultaneous apoptosis imaging - Chuandong Ge; Zhe Chen; Heming Sun; Ping Sun; Jiayin Zhao; Yanjuan Wu; Jing Xu; Mingyang Zhou; Mingming Luan (Analytica Chimica Acta, 2024)

An EGCG-mediated self-assembled micellar complex acts as a bioactive drug carrier - Chao Liu; Hao Wu; Hongxia Duan; Yan Hou; Shuangqing Wang; Yanhong Liu; Xintong Zhang; Heming Zhao; Liming Gong; Hongshuang Wan; Bowen Zeng; Xiuquan Quan; et al. (Food Chemistry, 2023)

Shear deformation calculation of landslide using distributed strain sensing technology considering the coupling effect - Lei Zhang; Yifei Cui; Honghu Zhu; Han Wu; Heming Han; Yan Yan; Bin Shi (Landslides, 2023)

Influence of spatial resolution of PM2.5 concentrations and population on health impact assessment from 2010 to 2020 in China - Heming Bai; Huiqun Wu; Wenkang Gao; Shuai Wang; Yang Cao (Environmental Pollution, 2023)

Materials footprint of household consumption in China - Jingru Liu; Haotong Wu; Xin Tian; Heming Wang; Yinglei Wu (Journal of Industrial Ecology, 2022)
China has been witnessing profound changes in the consumption behaviors of its population during the last several decades. To better gauge the current consumption structure of Chinese households and investigate the burden exerted by consumption on resources, we calculated the household material footprint (HMF) in China within the individual consumption classification framework developed by the United Nations. HMF is the only life‐cycle‐based indicator adopted into the 2030 Agenda for Sustainable Development. Four types of raw materials and 15 representative consumption divisions were analyzed in this research. The total HMF in China increased by 103% from 1992 to 2017, although the per capita HMF remains lower than the global average. The per capita HMF growth in rural and urban areas differs, with urban citizens consuming 2.8 more metric tons of resources than rural residents as of 2017. The HMF of all materials studied shows a rising trend, especially for metal ores, which underpins the real estate and auto industries. Food‐related consumption is the main contributor to the HMF in China, while consumption of housing and transportation has less proportion yet more growth potential compared with developed countries. This study adds to the literature of studies on the consumption behaviors and domestic demands of China and has further methodologically significant meaning for similar studies in other countries and practical value for policymakers. Overall, this study demonstrates that despite an upsurge in consumption behaviors and gratifying economic records, the incurred resource and environmental burden may fuel risks for sustainable development.

Histamine H1 Receptor in Basal Forebrain Cholinergic Circuit: A Novel Target for the Negative Symptoms of Schizophrenia? - Shuangshuang Wu; Chenshu Gao; Feng Han; Heming Cheng (Neuroscience Bulletin, 2022)

Spatiotemporal dynamics and influencing factors of the global material footprint - Heming Wang; Yao Wei; Yueming Wu; Xinzhe Wang; Yao Wang; Guoqiang Wang; Qiang Yue (Environmental Science and Pollution Research, 2022)

Inhibiting cyprinid herpesvirus-3 replication with CRISPR/Cas9 - Yicheng Zhao; Tiedong Wang; Ze Yu; Heming Wang; Bo Liu; Chunyan Wu; Chun-Bo Teng (Biotechnology Letters, 2016)

Polymorphism of follicle stimulating hormone beta (FSHβ) subunit gene and its association with litter traits in giant panda - Xiaoyu Huang; Desheng Li; Jiwen Wang; Yan Huang; Chunchun Han; Guiquan Zhang; Zhi Huang; Honglin Wu; Ming Wei; Guosong Wang; Haiping Hu; Tao Deng; et al. (Molecular Biology Reports, 2013)